Aedes albopictus may not be vector of dengue virus in human epidemics in Brazil - Degallier Nicolas; Teixeira José Marcus Sócrates; Soares Sidinei da Silva; Pereira Regilene D; Pinto Santuzza C F; Chaib Antonio de Jesus Melo; Vasconcelos Pedro F C; Oliveira Enilce (Revista de Saúde Pública, 2003)
Over 60,500 dengue cases were reported in the state of Espírito Santo (ES), Brazil, between 1995 and 1998. The study's purpose was to identify whether Aedes albopictus was transmitting the dengue virus during an epidemic in the locality of Vila Bethânia (Viana County),Vitória, ES. From April 3 to 9, 1998, blood and serum samples were collected daily for virus isolation and serological testing. Four autochthonous cases were confirmed through DEN 1 virus isolation and two autochthonous cases through MAC ELISA testing. Of 37 Ae. aegypti and 200 Ae. albopictus adult mosquitoes collected and inoculated, DEN1 virus was isolated only from a pool of two Ae. aegypti female mosquitoes. The study results suggest that Ae. albopictus still cannot be considered an inter-human vector in dengue epidemics in Brazil.